2017
DOI: 10.3945/ajcn.117.158964
|View full text |Cite
|
Sign up to set email alerts
|

Taurolidine-citrate-heparin lock reduces catheter-related bloodstream infections in intestinal failure patients dependent on home parenteral support: a randomized, placebo-controlled trial

Abstract: In patients with intestinal failure who are receiving home parenteral support (HPS), catheter-related bloodstream infections (CRBSIs) inflict health impairment and high costs. This study investigates the efficacy and safety of the antimicrobial catheter lock solution, taurolidine-citrate-heparin, compared with heparin 100 IE/mL on CRBSI occurrence. Forty-one high-risk patients receiving HPS followed in a tertiary HPS unit were randomly assigned in a double-blinded, placebo-controlled trial. External, stratifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
59
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 44 publications
0
59
1
3
Order By: Relevance
“…Overall, CRBSI rates had a significantly declining incidence toward recent years. By 2013 and thereafter, every patient has received taurolidine CVC locks reported to prevent CRBSIs also in other pediatric IF centers, a result confirmed recently in a randomized placebo‐controlled trial in adult patients with IF . We have used commercially manufactured 3‐in‐1 PN bags since 2011, likely also contributing to our currently low CRBSI rates .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Overall, CRBSI rates had a significantly declining incidence toward recent years. By 2013 and thereafter, every patient has received taurolidine CVC locks reported to prevent CRBSIs also in other pediatric IF centers, a result confirmed recently in a randomized placebo‐controlled trial in adult patients with IF . We have used commercially manufactured 3‐in‐1 PN bags since 2011, likely also contributing to our currently low CRBSI rates .…”
Section: Discussionmentioning
confidence: 69%
“…By 2013 and thereafter, every patient has received taurolidine CVC locks reported to prevent CRBSIs also in other pediatric IF centers, 7 a result confirmed recently in a randomized placebo-controlled trial in adult patients with IF. 34 We have used commercially manufactured 3-in-1 PN bags since 2011, likely also contributing to our currently low CRBSI rates. 35 Despite the standardized CVC care policy, certain individuals with SBS experienced repeated culturepositive line infections, which may also originate from inflamed small intestine with dysfunctional epithelial barrier of dilated remaining small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…involving 19 GI patients on home parenteral nutrition, CLABSI was reduced from 8.6 to 1.1 per 1000 catheter‐days with TCS usage . In a randomised controlled trial of 41 adult GI patients on home parenteral nutrition on taurolidine–citrate–heparin versus heparin, no CLABSI occurred in the TCS arm versus 1 per 1000 catheter‐days in the heparin arm . It has been proposed that TCS should only be used in home parenteral nutrition patients with high baseline rates of CLABSI.…”
Section: Discussionmentioning
confidence: 99%
“…Catheter‐related bloodstream infections (CRBSIs) are an oft‐encountered complication in patients receiving home parenteral nutrition (HPN). Two randomized clinical trials (RCTs) have shown that, compared with the use of heparin, when taurolidine is used in the catheter lock, fewer CRBSIs occur . Taurolidine, derived from taurine, interferes with the adherence of microorganisms, thereby preventing their subsequent local growth .…”
mentioning
confidence: 99%
“…Two randomized clinical trials (RCTs) have shown that, compared with the use of heparin, when taurolidine is used in the catheter lock, fewer CRBSIs occur. 1,2 Taurolidine, derived from taurine, interferes with the adherence of microorganisms, thereby preventing their subsequent local growth. 3 As should be appreciated, however, comparing taurolidine to heparin only demonstrates the relative efficacy of 2 interventions; 4 if heparin is actually harmful, we do not know if taurolidine is more effective than doing nothing.…”
mentioning
confidence: 99%